Low mutation rate of spontaneous mutants enables detection of causative genes by comparing whole genome sequences - Suganami, Mao; Kojima, Soichi; Yoshida, Hideki; Mori, Masaki; Kawamura, Mayuko; Koketsu, Eriko; Matsuoka, Makoto (Frontiers in Plant Science, 2024)
In the early 1900s, mutation breeding to select varieties with desirable traits using spontaneous mutation was actively conducted around the world, including Japan. In rice, the number of fixed mutations per generation was estimated to be 1. 38-2.25. Although this low mutation rate was a major problem for breeding in those days, in the modern era with the development of NGS technology, it was conversely considered to be an advantage for efficient gene identification. In this paper, we proposed an in silico approach using next-generation sequencing (NGS) to compare the whole genome sequence of a spontaneous mutant with that of a closely related strain with a nearly identical genome, to find polymorphisms that differ between them, and to identify the causal gene by predicting the functional variation of the gene caused by the polymorphism. Using this approach, we found four causal genes for the dwarf mutation, the round shape grain mutation and the awnless mutation. Three of these genes were the same as those previously reported, but one was a novel gene involved in awn formation. The novel gene was isolated from Bozu-Aikoku, a mutant of Aikoku with the awnless trait, in which nine polymorphisms were predicted to alter gene function by their wholegenome comparison. Based on the information on gene function and tissue-specific expression patterns of these candidate genes, Os03g0115700/LOC_Os03g02460, annotated as a short-chain dehydrogenase/reductase SDR family protein, is most likely to be involved in the awnless mutation. Indeed, complementation tests by transformation showed that it is involved in awn formation. Thus, this method is an effective way to accelerate genome breeding of various crop species by enabling the identification of useful genes that can be used for crop breeding with minimal effort for NGS analysis.